Classes multisseriadas: práticas, memórias e formação docente - OLIVEIRA, Mara Rita Duarte de (Universidade Federal do Pará, 2020)
This is research aimed to examine the pedagogical practices of teachers in multigrade classes, school " eld, located in the Municipality of Igarapé-Miri. We conducted the systematization of experiences by teachers in the classroom relating what teachers know, how they produce their teachers, cultural and pedagogical knowledge, as these transmit knowledge produced within their practices. We use information provided by these subjects through interviews as memorialistic narratives, we follow the school routine of schools, as well as visit the rural communities in which these schools are located.